Prawn fishery by the sona boats at Visakhapatnam - Rao, G Sudhakara (Indian Journal of Fisheries, 2011)
The catch of prawns per hour of trawling along the Visakhapatnam coast (cph)by sona boats (43'OAL) gradually increased from 1.70 kg in 1993-'94 to 2.96kg in 1996-'97. Prawns were landed throughout the year with the main seasonduring July-December. The peaks in the fishery varied in different years.Metapenaeus monoceros dominated forming 23.6-30.3 % of the annual landingsin different years followed by M. dobsoni (12.2-34.5 %), M. affinis (3.0-18.4 %),P. indicus (7.9-14.5 %), P. monodon (3.0-5.8 %) and P. semisulcatus(0.7-1.0 %). M. affinis and P. monodon indicated overfishing tendencies whileall the other commercial species maintained the stocks in a healthy state. Sincesona boat is more cost-effective than the small mechanised boats, mini trawlersand large trawlers, it has become a threat to these boats. Hence it is suggestedthat there should be a restriction on further increase in the number of sonaboats not only at Visakhapatnam but also at Paradeep and Kakinada to savethe other fleets operating for prawns